ANALISIS PERSEPSI NASABAH BMT MASLAHAH CAPEM GENDING DALAM PEMBERDAYAAN USAHA MIKRO - Ginan Nafsih; Robiatul Adawiyah; Zahida I'tisoma Billah (STKIP PGRI SITUBONDO, 2022)
This research was conducted to find out how the customer's perception of BMT in empowering micro-enterprises and the potential possessed by businesses that have financing in Baitul mal wa tamwil (BMT) for development in their economic activities in order to provide positive, prosperous and of course more Independent things.This research is a qualitative research using a descriptive study. The data of this research is teken from primary data, namely customer perceptions and secondary statements that can be trusted. Data collection techniques in the form of interviews (interviews), observation and documentation with the parties involved as well as information from books, articles, journals and theses.The results showed that the Baitul mal wa tamwil (BMT) capem Gending has an important role in empowering micro-enterprise, namely in term of financing provided in accordance with the Shari'a and work operasional contracts in service cooperatives where students make members feel satisfied and the requirements are easy, unlike other institutions. other finance BMT assists in the development of micro enterprises for customer.